2019
DOI: 10.1186/s12884-019-2560-8
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and poor birth outcomes in a diverse, low-income sample

Abstract: BackgroundAdverse childhood experiences (ACE) are associated with an array of health consequences in later life, but few studies have examined the effects of ACEs on women’s birth outcomes.MethodsWe analyzed data gathered from a sample of 1848 low-income women who received services from home visiting programs in Wisconsin. Archival program records from a public health database were used to create three birth outcomes reflecting each participant’s reproductive health history: any pregnancy loss; any preterm bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…Our study contributes to the growing evidence base linking ACE exposure with adverse health outcomes among perinatal populations. A growing number of researchers have applied a life-course perspective to the study of maternal and child health [ 6 , 51 ], due, in part, to increased recognition of the intergenerational transmission of maternal adversity and its sequelae. Greater understanding of the risks that ACE exposure poses both to adversity-exposed women and their infants is critical for appropriate assessment and intervention efforts to improve maternal and child health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study contributes to the growing evidence base linking ACE exposure with adverse health outcomes among perinatal populations. A growing number of researchers have applied a life-course perspective to the study of maternal and child health [ 6 , 51 ], due, in part, to increased recognition of the intergenerational transmission of maternal adversity and its sequelae. Greater understanding of the risks that ACE exposure poses both to adversity-exposed women and their infants is critical for appropriate assessment and intervention efforts to improve maternal and child health.…”
Section: Discussionmentioning
confidence: 99%
“…Women exposed to ACEs are over-represented among those who have adverse birth outcomes, including miscarriage [ 3 , 4 ], shortened gestational period and low birthweight [ 5 , 6 ]. They also are at increased risk for perinatal depression and anxiety [ 7 , 8 ] as well as other chronic health conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within low socioeconomic samples, adverse childhood experiences (ACEs), de ned as child maltreatment and exposure to household dysfunction before 18 years of age, are strongly associated with illicit drug use in pregnancy, as well poor birth outcomes more generally. 28,29 For example, a study of single, low income, African American women found the association between having three or more ACEs and illicit drug use in pregnancy was strong (OR of 6) and dose-dependent. 24 While it is often assumed that the impact of ACEs on illicit drug use is reduced among pregnant women with average to high socioeconomic status, this assumption is not well tested in the scienti c literature.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 12 16 Other variables, such as stress and adverse childhood experiences, may mediate some of these associations, because they are also more prevalent among Black people when compared with other racial groups. 17 – 23 Higher adverse childhood experience scores are associated with a greater likelihood of pregnancy loss, preterm birth, and perinatal depression, 24 26 but the relationship between race, adverse childhood experience, and pregnancy-related morbidity has only recently been explored. 24 , 27 …”
mentioning
confidence: 99%
“…17 – 23 Higher adverse childhood experience scores are associated with a greater likelihood of pregnancy loss, preterm birth, and perinatal depression, 24 26 but the relationship between race, adverse childhood experience, and pregnancy-related morbidity has only recently been explored. 24 , 27 …”
mentioning
confidence: 99%